Domestic violence among pregnant women attending antenatal clinics in Madi municipality, Chitwan, Nepal - Poudel, Eak Narayan; Koirala, Subash; Shrestha, Niki; Khanal, Gayatri; Chhetri, Mamta (Journal of Chitwan Medical College, 2021)
Background: Gender Based Violence (GBV) is a public health issue and is recognized as serious violence of human right worldwide. It is an ongoing social injustice to women. The impact of domestic violence on pregnant women is increasingly recognized as an important public health issue that has serious consequences for their physical and mental health. Hence the present study aimed to explore prevalence and predictors of Gender Based violence. Methods: The hospital based cross-sectional study using face to face interview was carried out in All – Healthcare Centers of Madi Municipality of Chitwan District, Nepal. 215pregnant women attending Antenatal clinics (ANC)were selected for study. We used Pearson’s chi-square test to investigate the effect of explanatory variables on domestic violence among pregnant women by using IBM Statistical software version 20. Results: Among 215 pregnant women attending Antenatal clinics there were 68.4% (147) pregnant women who faced any kind of domestic violence (either sexual or physical or emotional). Result shows that the domestic violence among pregnant women differ significantly with age group(χ2=6.46, p = 0.039) , education level of respondent(χ2= 12.45, p = 0.002) , occupation (χ2=11.3, p = .001) , family income(χ2= 13.4 , p=0.014) , presence of own property (χ2= 6.80, p = 0.033) , interest for pregnancy (χ2= 14.03, p < 0.001), husband’s consumption of alcohol (χ2= 25.94 , p<0.001). Conclusions: Prevalence of domestic Violence among pregnant women was found unacceptably high which ultimately foster risk to the mother and fetus health. Factors like age, educational level of the pregnant, family income, husband drinking alcohol habit and interest of the pregnancy among couple had profound relationship with domestic violence.